Redesign of Corporate Financial Architecture and Value of Companies Listed on the IDX Post-Covid-19 - WIDNYANA, I Wayan; BUDIYASA, I Gede Putu Eka (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:The COVID-19 pandemic has caused tremendous uncertainty in the business world, so companies are required to adjust their financial strategies. This study aims to examine the influence of the redesign of the Company's financial architecture—including the ownership structure, capital structure, and corporate governance on the value of companies listed on the Indonesia Stock Exchange (IDX) post-Covid-19 pandemic. The sample of this study consists of 200 companies.Methodology:The analysis technique used is multiple linear regression analysis. This study uses a quantitative approach with an analytical descriptive research design. The quantitative approach was chosen because it aims to measure the influence of certain variables numerically, especially the influence of financial architecture redesign on the value of companies listed on the Indonesia Stock Exchange (IDX) post-Covid-19 pandemic. To test the relationship between variables, multiple linear regression analysis method was used. The population in this study is all companies listed on the Indonesia Stock Exchange (IDX) in the period 2020 to 2023.Findings:The results of this study show that changes in capital structure and corporate governance post-COVID-19 have a significant impact on the value of the company, while changes in ownership structures tend to have a more limited effect.Implication:This study shows that the redesign of ownership structures, optimal capital structures, and improvement of corporate governance have a significant influence on the value of companies listed on the Indonesia Stock Exchange post-Covid-19 pandemic.